Melioidosis presenting with acalculous cholecystitis and acute pyelonephritis - S. Rupasinghe; W. K. S. Kularatne (Asian Journal of Internal Medicine)
Melioidosis is an infection caused by a gram-negative bacterium, which is widely distributed in fresh surface water and soil in endemic regions. Melioidosis occurs predominantly in Southeast Asia, South Asia, northern Australia and China. Fatal melioidosis commonly occurs in individuals with specific comorbidities including diabetes mellitus, harmful use of alcohol, chronic lung disease and chronic kidney disease. The most common acute manifestation is pneumonia. Other sites of infection include skin, soft tissue and genitourinary tract. We present a case of melioidosis in a 52-year-old farmer presenting with acalculous cholecystitis and acute pyelonephritis which was successfully treated with antibiotics.